Adaptation of the State-Trait Inventory for Cognitive and Somatic Anxiety for Use in Children: A Preliminary Analysis. (25th April 2016) - Deacy, Amanda D.; Gayes, Laurie A.; De Lurgio, Stephen; Wallace, Dustin P.
Abstract : Objective Anxiety has both state/trait and cognitive/somatic dimensions, and these distinctions may be particularly relevant for children with medical problems. This two-part study adapted the State-Trait Inventory for Cognitive and Somatic Anxiety (STICSA) and confirmed its factor structure in a sample of children in a primary care clinic. Methods STICSA items were adapted for reading level and piloted in a small group of children. Next, 250 children (12.3 ± 2.7 years) completed the adapted version, the STICSA-C. Results Separate confirmatory factor analyses conducted on the State and Trait forms of the STICSA-C confirmed the two-factor structure of the original measure (i.e., cognitive and somatic anxiety) and suggested an improved parsimonious model. Conclusions Support was found for use of the STICSA-C as a reasonably good internally consistent measure for assessing cognitive and somatic anxiety in pediatric samples. Further investigation of its reliability and validity with replication in pediatric populations is warranted.